2013
DOI: 10.1111/sji.12055
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL‐1β +3954 C/T and IL‐10‐1082 G/A Cytokine Gene Polymorphisms with Susceptibility to Tuberculosis

Abstract: Tuberculosis (TB) constitutes the major cause of death due to infectious diseases. Cytokines play a major role in defence against Mycobacterium tuberculosis infection. Polymorphisms in the genes encoding various cytokines have been associated with tuberculosis susceptibility. Household contacts (HHC) are at increased risk of developing the disease. In this study, we examined the association of IL-1b and IL-10 cytokine gene polymorphisms with risk of developing tuberculosis in TB patients, their HHC and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…Previous studies have reported that cytokine genes contribute to susceptibility of TB, such as interferon-1β, interleukin (IL)-3, IL-6, IL-10, and IL-12B IL-17 as well as IL-18 (Selvaraj et al, 2008;Abhimanyu et al, 2011;Meenakshi et al, 2013;Feng et al, 2014;Tiwari et al, 2014;Zhang et al, 2014). However, the results have been inconsistent.…”
Section: Introducioncontrasting
confidence: 40%
“…Previous studies have reported that cytokine genes contribute to susceptibility of TB, such as interferon-1β, interleukin (IL)-3, IL-6, IL-10, and IL-12B IL-17 as well as IL-18 (Selvaraj et al, 2008;Abhimanyu et al, 2011;Meenakshi et al, 2013;Feng et al, 2014;Tiwari et al, 2014;Zhang et al, 2014). However, the results have been inconsistent.…”
Section: Introducioncontrasting
confidence: 40%
“…There are 29 case-control studies concerning -1082G/A polymorphism [16]–[44], 14 case-control studies concerning -819T/C polymorphism [16], [18], [20][23], [25], [31], [33], [37]–[39], [42], [45], and 16 case-control studies concerning -592A/C polymorphism [16], [20][25], [28], [31], [33], [37][40], [45], [46]. Among the 31 eligible studies, 17 of them were of Asians [16], [18], [19], [26], [28], [30][32], [34], [36], [39], [41]–[44], [46], 6 studies were of Europeans [17], [21], [25], [27], [35], [37], 5 studies were of Africans [20], [22], [29], [33], [38], and 3 studies were of Americans [23], [24], [40]. Controls were selected from healthy population in all studies and most studies used frequency-matched controls to the cases by age, sex, or ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…1. The search of the selected databases retrieved 15 potentially relevant articles (Amirzargar et al, 2006;Bellamy et al, 1998;Wilkinson et al, 1999;Delgado et al, 2002;Awomoyi et al, 2005;Gomez et al, 2006;Sun et al, 2007;Naslednikova et al, 2009;Trajkov et al, 2009;Meenakshi et al, 2013;Oral et al, 2006;Henao et al, 2006;Selvaraj et al, 2008;Ansari et al, 2011;Zhang et al, 2012), including 3983 cases and 3996 controls, according to inclusion and exclusion criteria. There were 7 case-control studies concerning IL1β +3953C/T polymorphism, 8 case-control studies for IL1β-511T/C polymorphism, and 7 case-control studies about IL-6 − 174G/C polymorphism.…”
Section: Literature Search and Characteristics Of Eligible Studiesmentioning
confidence: 99%